Fear of Missing Out (FoMO) dan Implikasinya terhadap Perilaku Konsumtif Mahasiswa pengguna Online Shopping di Kota Ternate. - Vicaletvia; Novi Elisadevi (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze Fear of Missing Out (FOMO) and its implications for the consumer behavior of college students who use online shopping in Ternate City. The study sample consisted of 327 college students in Ternate City. The research design employed a sequential explanatory strategy, with quantitative data collection and analysis in the first stage, followed by qualitative data collection and analysis in the second stage. Data were collected using the Fear of Missing Out (FoMO) scale, the Consumption Behavior scale, and an interview guide developed by the researcher. Data analysis techniques included linear regression analysis for quantitative data and thematic analysis for qualitative data. The results of this study indicate that 18% of consumptive behavior can be explained by FoMO. The interview results identified several factors influencing consumptive behavior, including self-confidence, stress coping, self-control, and social recognition.